Study on the Consumer Acceptance to theSmoke Flavored Steak (Fillet) White Snapper Fish - Enrawana Putri Purba; Mirna Ilza; Tjipto Leksono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was purposed to determine the effect of different concentrations of soaking liquid smoke on consumer acceptance to the smoke flavored steak (fillet) white snapper fish. The method used was experiment and composed ascompletely randomized design. The treatment factor was soaking steak/ fillet into solution of liquid smoke at different concentrations, namely: 0 % as control (Sa0) 3% (Sa3) and 6% (Sa6) for 1 hour then grilled. Parameters used were organoleptic value, total number of bacterial colony, pH, content of acids and phenols, and the proximate composition. The results showed that the best treatment of soaking fish into liquid smoke at concentration of 3% (Sa3) wasresulting to the highest consumer acceptance to the smoke flavored steak (fillet) white snapper fish produced. The characteristics of the best product were interesting golden brown colored, distinctive aroma of liquid smoke but not too strong, tasted very delicious and typical of the smoke, and the texture was compact and solid, with total number of bacterial colonies of 6.6X104cfu/g, pH of 6.64, content of acids2.09%, phenols of 4.35%, and contained moisture of 61.4%, protein of 28%, and fat of 4.2%.Keywords :Lates calcarifer, liquid smoke, snapper fish, steak (fillet)